2023
DOI: 10.1186/s12866-023-02922-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and antifungal activity of lipopeptides produced from Bacillus subtilis against plant fungal pathogen Alternaria alternata

Abstract: Over 380 host plant species have been known to develop leaf spots as a result of the fungus Alternaria alternata. It is an aspiring pathogen that affects a variety of hosts and causes rots, blights, and leaf spots on different plant sections. In this investigation, the lipopeptides from the B. subtilis strains T3, T4, T5, and T6 were evaluated for their antifungal activities. In the genomic DNA, iturin, surfactin, and fengycin genes were found recovered from B. subtilis bacterium by PCR amplification. From dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…p-Cymene, also known as p-isopropyl toluene, is a naturally occurring alkyl-substituted aromatic chemical found in essential oils of various medicinal and aromatic plants, as well as several edible plants. Studies have revealed that p-cymene has antioxidant, anti-inflammatory, antiparasitic, antidiabetic, antiviral, anticancer, antibacterial, and antifungal effects ( Harish et al, 2023 ). Additionally, p-cymene has been associated with analgesic, antinociceptive, immunomodulatory, vasorelaxant, and neuroprotective properties ( Verruck et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…p-Cymene, also known as p-isopropyl toluene, is a naturally occurring alkyl-substituted aromatic chemical found in essential oils of various medicinal and aromatic plants, as well as several edible plants. Studies have revealed that p-cymene has antioxidant, anti-inflammatory, antiparasitic, antidiabetic, antiviral, anticancer, antibacterial, and antifungal effects ( Harish et al, 2023 ). Additionally, p-cymene has been associated with analgesic, antinociceptive, immunomodulatory, vasorelaxant, and neuroprotective properties ( Verruck et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…A sixfold dilution of cell‐free supernatant of B. vallismortis T27 showed a complete inhibitory effect on Valsa mali hyphae growth, and treatment with T27 resulted in a 35.9% reduction in lesion areas on detached twigs 9 . Compared to the other three, B. subtilis T6 had the higher antifungal activity against A. alternata (85.88%), which can infect more than 380 host plants, and cause rots, blights and leaf spots on different plant sections 10 . In addition, Bacillus , known as a plant–growth‐promoting rhizobacteria (PGPR), has been studied under greenhouse and field conditions, and has shown many significant traits and properties, including secreting indole‐3‐acetic acid (IAA) and phosphate solubilization, which allow direct growth promotion in plants 11 .…”
Section: Introductionmentioning
confidence: 94%
“…9 Compared to the other three, B. subtilis T6 had the higher antifungal activity against A. alternata (85.88%), which can infect more than 380 host plants, and cause rots, blights and leaf spots on different plant sections. 10 In addition, Bacillus, known as a plant-growth-promoting rhizobacteria (PGPR), has been studied under greenhouse and field conditions, and has shown many significant traits and properties, including secreting indole-3-acetic acid (IAA) and phosphate solubilization, which allow direct growth promotion in plants. 11 B. subtilis FJ3 and its metabolites caused 24.01% and 10.46% growth promotion in chickpea, respectively.…”
Section: Introductionmentioning
confidence: 99%